THE ROLE OF DIFFERENTIATED EDUCATION IN IMPROVING THE CREATIVE ABILITIES OF STUDENTS. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
this article also talks about the role of the teacher in the development of skills and abilities in the development of games on the basis of school children and in the work of composition on the basis of the topic. the development of skills for students to work in composition on the basis of the topic is covered as a pedagogical problem.